PENGARUH WAKTU FERMENTASI TERHADAP PERSENTASE PENYISIHAN PADATAN TERSUSPENSI TOTAL (TSS) CAMPURAN LIMBAH CAIR INDUSTRI TAPIOKA DENGAN AIR - Wan Rizki Ansari, Umayi Belladiana, Setiaty Pandia (Universitas Sumatera Utara, 2014)
The waste water of tapioca is the waste produced from the washing process raw materials, screening cassava porridge (extraction) and starch sediment containing organic compounds which are still important, especially starch and other compounds that can be used as raw material for the manufacture of bio gas. This study aimed to determine the effect of fermentation time on the elimination percentage of Total Suspended Solid (TSS) using batch anaerobic digester system. Research was carried out by mixing the liquid waste of tapioca industry with water in the ratio 100:0; 85:15; 65:35; 50:50;35:65, and 15:85 (v/v) with starterin an anaerobic digester system batch in which neutral pH of the mixture was set. Parameter observed was the content of Total Suspended Solid. Percentage of elimination of Total Suspended Solid was reached at the rasio of liquid waste to water 100:0 (v/v) with the optimal value of 89.851% on the 21th day.